Metabolic Syndrome is Related to Macronutrient Intake in a Medan Vegetarian Community in North Sumatera Indonesia - Siahaan; Ginta; Lestrina, Dini; Nainggolan, Effendi (Pakistan Journal of Nutrition, 2017)
Background and Objective: A vegetarian (vegan, lacto, ovo and lacto ovo) diet characterized by low intake of simple carbohydrates, cholesterol and fat and high intake of fiber can reduce the prevalence of degenerative diseases, particularly those related to metabolic syndrome. Metabolic syndrome is defined as fasting glucose>110 mg dL–1, triglyceride>150 mg dL–1, cholesterol25 and waist>90 cm for men and >80 cm for women. This study aimed to determine if metabolic syndrome is related to macronutrient intake in a Medan vegetarian community using an observation method with a cross-sectional design. Methodology: The population studied included all members of the vegetarian Maha Vihara Maitreya Medan community whose ages ranged between 30 and 58 years. Data was analyzed using pearson’s correlation. Results: The result showed that macro nutrient intake can reduce the rate of metabolic syndrome (p